Post-digital print : the mutation of publishing since 1894 - Ludovico, Alessandro (Eindhoven : Onomatopee, 2013)
Is print really dead, or is it going to die anytime soon? This books examines "a particular (and often puzzling) period in the history of print ... as new digital technologies are rapidly transforming both the status and the role of printed materials." The medium of print is without doubt under threat from new digital sources, yet the two are also finding a paradoxical coexistence despite their shared characteristics and functional competition. In some ways, print is actually nowadays being revitalized rather than replaced, an intriguing prospect which is explored in depth in the pages of this book.
boek